Modelling word-formation paradigms: networks visually representing their multidimensionality, complexity and theoretical infiniteness - Rodrigues, Alexandra Soares (2021)
Our work focuses on modelling word-formation paradigms. We propose that networks (Newman 2010) provide the means to model and visually represent word-formation paradigms. Networks enable us to represent paradigms at both the large scale and the small scale, bringing visual and conceptual evidence to the multidimensional relationships that shape paradigms (Štekauer (2014) and to the dynamics of the mental lexicon The relationships between the items of a paradigm can be founded on different features (Pounder 2000, van Marle 1985, Štekauer 2014), such as word class, semantic rules or formal features (Pounder labelled these features lexical paradigms). Štekauer (2014: 359) refers to semantic structures (AGENT, INSTRUMENT, ACTION) and to the formal realisation of these categories (suffixation in -ation, -ment, etc.). The feature that is responsible for cohesion among items of the paradigm is called the axis of the paradigm by Rodrigues & Rodrigues (2018). Bonami & Strnadová (2019: 170) use the term paradigmatic system to refer to relationships between pairs based on content (which includes syntactic and semantic categories). The term series is reserved for the relationships between pairs based on the share of a derivational affix (Hathout 2009). Bearing these aspects in mind, we consider that a network model serves as the basis to describe and visualise the multiple and complex relationships built within and by derivational paradigms.